The Construction of Legal Liability of BPJS Kesehatan and Hospitals for Pending Claims - Khalid, Hasbuddin; Hamzah, Yuli Adha; Ikhtiari, Athifa (Universitas Negeri Gorontalo, 2026)
Pending BPJS Kesehatan claims are often reduced to a purely administrative issue, even though this condition triggers complications of civil liability that have a systemic impact on the quality of healthcare services. This normative legal study aims to reconstruct the limits of the legal liability of the parties within the National Health Insurance (JKN) ecosystem by examining the intersection between the regimes of breach of contract and tortious acts (Perbuatan Melawan Hukum/PMH). The findings reveal a hierarchically distinct structure of civil liability within the triadic relationship of BPJS, hospitals, and patients. First, in the contractual sphere, the status of breach of contract is determined by the party that commits the first breach: BPJS is deemed to be in breach when it unilaterally delays payment of valid claims, whereas a hospital is deemed to be in breach when the delay originates from its administrative negligence. Second, in the sphere of service delivery, hospitals bear an absolute duty toward patients. A decline in the standard of care resulting from cash flow constraints caused by pending claims legally constitutes a tortious act by the hospital, and the burden of liability cannot be shifted to BPJS. This study contributes the conceptual proposition that patient protection must be isolated from the dynamics of contractual financing disputes. Therefore, a reformulation of the cooperation agreement is required to specifically regulate the separation of liability regimes and proportional dispute resolution mechanisms in order to eliminate inequality of position and overlap in civil obligations within the JKN system.